Penerapan Konten Pemasaran Digital dan Kemasan Berbasis Indigenous Product Creativity Pada Batik Serunai Melayu Riau di Kabupaten Kampar, Riau - Annisa Mardatillah; Lilis Marina Angraini; Elizar Elizar (PELANTAR PRESS, 2025)
This Community Service Program aims to gain the knowledge and skills Batik Serunai Melayu Riau in implementing digital marketing concepts and sustainable packaging based on indigenous product creativity. The activities were carried out through a series of stages, including counseling sessions, practical training, and direct mentoring for business partners, which consisted of one business owner and five workers. The training also covered strategies for promoting products digitally through the application of social media content and the use of packaging designs rooted in indigenous product creativity.The program further emphasized the integration of Malay cultural values into packaging design and marketing communication messages to strengthen product identity and improve customer recognition. Using an applied approach that combines education and hands-on practice, participants gained a deeper understanding of the importance of applying digital content in marketing media as a digital marketing strategy, as well as utilizing packaging materials that reflect local cultural identity. The partners consisted of artisans from Batik Melayu Serunai, including the owner and five employees. The program's result indicate that participants demonstrated improved understanding and ability to apply digital marketing strategies and sustainable packaging concepts grounded in the cultural values of Malay Riau